2012
DOI: 10.1183/09031936.00041212
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, nutritional status and systemic inflammation in COPD

Abstract: [No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 112 publications
1
32
0
2
Order By: Relevance
“…Another hypothesis supports the proposition that an enhanced expression of granulocyte-macrophage colony-stimulating factor and IL-6 in COPD plays an important role, as these mediators stimulate neutrophils release from the bone marrow causing an increased neutrophil amount in the peripheral blood [7], [8] . Systemic hypoxia due to progression of COPD has been suggested as a possibility [2] .…”
Section: Introductionsupporting
confidence: 61%
“…Another hypothesis supports the proposition that an enhanced expression of granulocyte-macrophage colony-stimulating factor and IL-6 in COPD plays an important role, as these mediators stimulate neutrophils release from the bone marrow causing an increased neutrophil amount in the peripheral blood [7], [8] . Systemic hypoxia due to progression of COPD has been suggested as a possibility [2] .…”
Section: Introductionsupporting
confidence: 61%
“…Patologie te z kolei są czynnikami ryzyka wystąpienia chorób sercowo-naczyniowych [48]. Obniżona aktywność ruchowa u części pacjentów z POChP także może wiązać się z rozwojem cukrzycy oraz patologii naczyniowych [49,50].…”
Section: Patogeneza Współistnienia Pochp I Chorób Sercowo-naczyniowychunclassified
“…One systematic review found that dietary supplementation improved body weight and grip strength [225], whereas another systematic review found nonsignificant trends toward a beneficial effect of nutritional supplementation on anthropometric measures, lung function and exercise capacity [226]. Alternative metabolic treatments, including androgens and human growth hormone, have also been tried, but their long-term effects remain unknown [227]. Micronutrients may also play a role in COPD.…”
Section: Nutritionmentioning
confidence: 99%